New virulence factor CSK29544-02616 as LpxA binding partner in Cronobacter sakazakii - Kim, Seongok; Yoon, Hyunjin; Ryu, Sangryeol (Scientific Reports, 2018)
Cronobacter sakazakii is an opportunistic pathogen that can cause meningitis and necrotizing enterocolitis in premature infants, but its virulence determinants remain largely unknown. In this study, a transposon-mediated random-mutant library of C. sakazakii was used to identify new virulence factors. Compared to wild-type bacteria, a mutant lacking CSK29544-02616 (referred to as labp) was defective in invasion into intestinal epithelial cells (by at least 1000-fold) and showed less phagocytosis by macrophages (by at least 50-fold). The lack of labp in C. sakazakii changed the profile of outer membrane proteins, decreased the production of lipopolysaccharides, and increased the production of membrane phospholipids. Bacterial physiological characteristics including surface hydrophobicity and motility were also altered in the absence of labp, presumably because of changes in the bacterial-envelope structure. To systematically determine the role of labp, ligand fishing was conducted using Labp as a bait, which revealed LpxA as a binding partner of Labp. LpxA is UDP-N-acetylglucosamine (GlcNAc) acyltransferase, the first enzyme in the pathway of lipid A biosynthesis. Labp increased the enzymatic activity of LpxA without influencing lpxA expression. Considering multifaceted roles of lipopolysaccharides in virulence regulation, Labp is a novel virulence factor that promotes the production of lipid A by LpxA in Cronobacter.
Keywords: Acyltransferases; Animals; Bacterial Outer Membrane Proteins; Cronobacter sakazakii; Epithelial Cells; HeLa Cells; Humans; Lipopolysaccharides; Macrophages; Mice; Mutagenesis, Site-Directed; Phagocytosis; Phospholipids; Protein Binding; Rats; Rats, Sprague-Dawley; RAW 264.7 Cells; Virulence Factors